“The non-acceptance of testamentary indivision as an exceptional and anti-dogmatic figure in the peruvian Civil Code” - Olavarría Vivian, Juan Alejandro (2025)
The Civil Code of 1984 contains some great contradictions, which generate difficult solutions to the common denominator of the people, as well as to those who must administer justice, since they are exposed to permanently deal with the interpretative range that our substantive code generates. In this article we analyze a contradiction that arises in the specific case of testamentary indivision and the possibilities and consequences of the non-acceptance of the same by the testamentary heirs, which can lead us to understand it contradictorily as a sort of partial waiver of the inheritance, certainly not allowed by law. We have made use of the solutions that have been found in foreign legislations, basically Argentina and Spain, to take references of the normative treatment and solution, as well as of our antecedents of the Civil Code of 1852 and the Civil Code of 1936, regarding the state of testamentary indivision.